Tolerance Practices: Between Family and Religious Solidarity: (Case Study of Chinese Ethnic Communities In The City of Surabaya) - Warsono, Warsono; Diba, Sofinadya; Nubail, Ahmad (The Journal of Society and Media, 2023)
Social conflicts originating from religious differences in Indonesia often occur between adherents of different religions and followers of the same faith. Though the ethnic Chinese community in Surabaya has different religions, they can foster positive behavior by respecting, accepting, and appreciating each other. This phenomenon is different from Conflicts between adherents of different religions that occurred in Tolikara District; conflicts caused by belief (religion) also appeared in Sampang and others. This study aims to explore the problem of religious difference conflict so that there is a solution. This research uses a qualitative approach designed to study the state of objects naturally. The theory used in this study is the theory of Cultural Pluralism. The result of this research is that the Chinese have various uniqueness, especially their religious tolerance, which various minorities in other cities should emulate. For them, religion is a human right of every person, so it does not become a barrier to interacting with one another